Auditing the socio-environmental determinants of motivation towards physical activity or sedentariness in work-aged adults: a qualitative study. (December 2016) - Keegan, Richard; Middleton, Geoff; Henderson, Hannah; Girling, Mica
Abstract Background There is a lack of understanding of work aged adults' (30–60 years old) perspectives on the motivation of physical activity versus sedentariness. This study aims to: (1) identify which socio-environmental factors motivate physical activity and/or sedentary behavior, in adults aged 30–60 years; and (2) explore how these motivators interact and combine. Method Fifteen work-aged adults who, were able to engage in physical activity (Mean age = 43.9 years; SD 9.6, range 31–59), participated in semi-structured interviews. Inductive content analysis was used to generate an inventory of socio-environmental factors and their specific influences on motivation towards physical activity or sedentariness. Results Key socio-environmental agents found to influence motivation included: Spouse/partner, parents, children, siblings, whole family, grandchildren, friends, work-mates, neighbors, strangers, team-mates and class-mates, instructors, health care professionals, employers, gyms and health companies, governments, media and social media, cultural norms, and the physical environment. Mechanisms fell into five broad themes of socio-environmental motivation for both physical activity and sedentariness: (1) competence and progress; (2) informational influences, (3) emotional influences, (4) pragmatics and logistics, and (5) relationships. Similar socio-environmental factors were frequently reported as able to motivate both activity and sedentariness. Likewise, individual categories of influence could also motivate both behaviors, depending on context. Conclusion The findings of this paper 'unpack' theoretical concepts into specific and targeted behavioral recommendations. The data suggested no simple solutions for promoting physical activity or reducing sedentariness, but rather complex and interacting systems surrounding work-aged adults. Findings also suggest that health professionals should be encouraged to support adults' health by examining the socio-environmental motivational influences, or 'motivational atmosphere'.